Interculturality and feminisms at Universidad Veracruzana Intercultural to counteract gender discrimination and violence (Praxis Educativa, 2022)
research, in this text I systematize a portion of the academic work at the Universidad Veracruzana Intercultural campus Grandes Montañas (UVI-GM) between the years 2010 and 2021. This trajectory links both the feminist and the intercultural views. The work has been focused in our substantial functions: teaching, promoting students’ integral development activities, directing professional examination works, tutoring, giving lectures and seminars, as well as designing and implementing institutional formative programs. Also, canvassing community players and civil organizations has made possible to face the issues of violence and discrimination towards women. In other words, besides working on preventing, we have also assessed and addressed students in specific situations. The situation originated by the Covid 19 pandemic has forced us to update and rethink these tasks.
Keywords: critical interculturality; partnered research; gender discrimination; gender violence; feminisms at the university